Kinematic responses of vehicular passenger duri (with and without restraint of various types) - Soh, Zi Haur. (2010)
As the number of vehicles on the road increases, the number of road related injuries and deaths rises as well. Therefore, it is of significance to understand the types of deadly injuries that can happen to road users as a result of road traffic accidents. The project entails the use of simulation software, Articulated Total Body (ATB) which allows the user to predict the kinematic responses and impacts to the occupant due to a vehicle collision by modeling dynamically the different segments of the body seated in a vehicle initially.